SELF-IDENTIFICATION OF PRECARIAT REPRESENTATIVES - Oliynyk, Ivan; Bezprozvanna, Tatiana; Maletska, Maria (Skhid, 2020)
This article is devoted to the self-identification of precariat representatives. The study on the identity is relevant due to the fact that for precariat, which lives in total instability and uncertainty, such factor of stabilization is much more important than for other social groups. The purpose of the article is to delineate self-identification features of precariat representatives. A cross-methodological approach has been used to achieve this purpose, including: systemic, comparative methods; method of synthesis and generalization of materials presented in the scientific literature on the researched problem. The main defining characteristics of precariat have been disclosed, including the lack of the work-based and occupational identity. It is concluded that the lack of work-based and occupational identity makes it more difficult to form a class consciousness of precariat, which, in turn, impedes the establishment of precariat as a “class-for-itself”. Nowadays, the formation of identity is often replaced with self-branding. Self-branding, however, does not contribute to the formation of stable self-identification that may be helpful in stabilization of social positions and removal of instability and uncertainty. It often leads to replacing people with things they buy and money they earn instead of identification with certain profession. The formation of precariat representatives’ self-identification is important to remove the uncertainty and instability, thus, to solve the problems of anxiety inherent in precariat. The studies on this problem can influence the economic and political spheres. The following studies on self-identification of precariat representatives in Ukraine is also relevant because it can help to understand the specificity of this class and its manifestations in our country.